PENGARUH VARIABEL KEUANGAN TERHADAP PROFITABILITAS BANK (STUDI EMPIRIS LEMBAGA PERBANKAN PADA BEI) - Utami, Puri Yunia; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The rapid development of economy has made all economic activities require banking services. The public demand on information of the condition of banking financial performance has to be published consecutively, so that the trust level from the public is maintained. This research is meant to analyze the bank performance by using non performimg loan, interest rate risk, cash ratio, net interest margin, and capital adequacy ratio to the dependent variable which in return on assets. This research uses purposive sampling technique and 15 banking companies which are listed in Indonesia Stock Exchange and have published their financial statement in 2011-2013 periods have been selected as samples, and have complete data about the variable which will be observed. The data is the secondary data which has been retrieved the financial data from the Indonesia Stock Exchange official website and the related bank website. The analysis data has been done by using multiple linier regressions analysis. The results of this research shows that non performing loan, and net interest margin has significant influence to the return on assets so that those hypothesis is accepted, where as interest rate risk, cash ratio, and capital adequacy ratio do not have any significant influence to the return on assets so that those hypothesis denied.Keywords: Non performing loan, interest rate risk, cash ratio, net interest margin, capital adequacy ratio, return on asset.